The Effects of Bone Cement Volume in Percutaneous Vertebroplasty for Thoracolumbar Junction Vertebral Compression Fractures: A Clinical Comparative Study - Meng Wang; Bo Li; Yuren Wang; Shengdan Jiang; Gen Wen; Leisheng Jiang; Xinfeng Zheng (Hindawi Limited, 2022)
We compared the outcomes of patients treated with different volumes of polymethyl methacrylate bone cement during percutaneous vertebroplasty (PVP) for thoracolumbar vertebral compression fractures. We performed a comparative, retrospective study of 316 patients who underwent PVP for a single-level thoracolumbar vertebral compression fracture. Patients were divided into two groups: group A (≤5 mL; n=146) and group B (>5 mL; n=170). The visual analogue scale (VAS) for pain and the Roland-Morris Disability Questionnaire (RDQ) scores were compared between the two groups at 1 week and at 1, 6, 12, and 24 months after PVP. The incidence of cement leakage into the intervertebral discs was evaluated by a postoperative lateral radiograph assessment. Patients were evaluated for new fractures 1 and 2 years after PVP or when new fractures were suspected. Among the 316 patients enrolled, 245 completed the clinical research. No difference between groups A and B in terms of the VAS, RDQ, and rate of complications at all time points after surgery was observed. The presence of intervertebral disc leakage was a relative risk (RR) for subsequent total vertebral fracture (RR, 6.42; 95% confidence interval (CI), 2.72-14.19; P<0.0001) and adjacent vertebral fracture (RR, 8.03; 95% CI, 2.74-23.54; P=0.0001). A high volume of bone cement may increase the rate of subsequent total and adjacent vertebral fractures. However, the occurrence of intervertebral disc leakage is the principal risk factor for these negative outcomes of PVP.